HIGH HYDROGEN SOLUBILITY IN Al-RICH STISHOVITE AND WATER TRANSPORT IN THE LOWER MANTLE - Litasov K.D.; Ohtani E.; Kagi H.; Shatskiy A.; Ito E.; Lakshtanov D.L.; Bass J.D. (My University, 2007)
Stishovite is an important phase in subducting oceanic crust. The post-garnet assemblage from a precursor eclogite lithology contains up to 25% stishovite at pressures above 25 GPa. This stishovite may contain up to 5 wt.% Al2O3. We measured the hydrogen contents of stishovite samples synthesized at 20-25 GPa and 1200-1800 °C from several starting materials containing up to 10 wt.% Al2O3. FTIR spectra of stishovite show major bands at 3111-3134 cm- 1, with the frequencies increasing as H2O and Al2O3 contents increase, and several minor bands at 2659-2667, 3240, 3261, 3312-3334, and 3351 cm- 1. The H2O content of Al-free stishovite is in the range of 16-30 wt. ppm. The maximum H2O content of Al-bearing stishovite (4.4 wt.% Al2O3) synthesized at 20 GPa and 1400 °C is 3010 ± 300 wt. ppm. Most hydrogen in stishovite is associated with Al3+ substitutional defects on the octahedral (Si4+) site. The hydrogen can occupy 40% of vacancies created by incorporation of Al3+ at 20 GPa. This observation along with some anomalies in the FTIR spectra may indicate an alternative mechanism of Al3+ incorporation into stishovite via the formation of oxygen vacancies or interstitial Ali{radical dot}{radical dot}{radical dot} defects. We report the highest H2O concentrations in Al-stishovite to date, and argue that it is the most important carrier of water into the lower mantle post-garnet eclogitic assemblages. © 2007 Elsevier B.V. All rights reserved.
Keywords: ECLOGITE; HYDROGEN; INFRARED SPECTROSCOPY; LOWER MANTLE; STISHOVITE